Population size, provisioning frequency, flock size and foraging range at the largest known colony of Psittaciformes: the Burrowing Parrots of the north-eastern Patagonian coastal cliffs - Masello, Juan F. (2006)
We here describe the largest colony of Burrowing Parrots (Cyanoliseus patagonus), located in Patagonia, Argentina. Counts during the 2001–02 breeding season showed that the colony extended along 9 km of a sandstone cliff facing the Altantic Ocean, in the province of Río Negro, Patagonia, Argentina, and contained 51412 burrows, an estimated 37527 of which were active. To our knowledge, this is largest known colony of Psittaciformes. Additionally, 6500 Parrots not attending nestlings were found to be associated with the colony during the 2003–04 breeding season. We monitored activities at nests and movements between nesting and feeding areas. Nestlings were fed 3–6 times daily. Adults travelled in flocks of up to 263 Parrots to the feeding grounds in early mornings; later in the day, they flew in smaller flocks, making 1–4 trips to the feeding grounds. Overall, the most frequent flock size was two, indicating that the pair is the basic social unit during the breeding season. The average flight-speed was 36.9 km h–1. Terrestrial and aerial surveys during the 2003–04 and 2004–05 breeding seasons suggest that Burrowing Parrots performed long daily movements in order to feed in the remaining patches of natural vegetation, travelling 58 and 66 km over the two main routes to the feeding areas. The colony is seriously threatened by human activity, and surrounding habitat is being rapidly transformed to agricultural land. Based on the data presented, we recommend monitoring the colony using detailed counts of numbers of nests, the documentation of the extent of the entire colony, together with data on breeding success, nestling growth and feeding rates. The number of non-breeders associated with the colony should be monitored, and as an additional index of abundance, counts from stationary locations should be continued.